Is Offshoring Beneficial or Detrimental to Innovation in Developed Countries? - Ursula Fritsch (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper empirically investigates the effects of offshoring on innovation in a sample of 18 developed countries. Offshoring of services relates positively to innovation whereas offshoring of manufacturing depicts a negative relation with innovation. Solely offshoring manufacturing to high-income countries is found to be detrimental to domestic innovation, but not offshoring of manufacturing to emerging countries. These results are robust to an instrumental variables approach. Labor market dynamics can mitigate or even reverse these negative effects of offshoring of manufacturing if skill upgrading takes place simultaneously. This paper documents that innovation effects differ from the positive productivity effects found in earlier research and suggests that policy makers should take these different effects into account when designing a regulatory framework for further trade integration.
Keywords: F14; F16; O30; 330